THE CONTRIBUTION OF "GURU PENGGERAK" IN REALIZING RELIGIOUS LEARNING - Irmayani (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
ABSTRACT Realizing religious learning involves integrating spiritual values, fostering moral character, and creating an environment that encourages faith-based practices and ethical behavior in education. The "Guru Penggerak" contributes by fostering a values-based learning environment, integrating religious principles into lessons, and promoting character-building activities aligned with spiritual values. Realizing religious learning involves integrating spiritual values, fostering moral character, and creating an environment that encourages faith-based practices and ethical behavior in education. Realizing religious learning involves integrating spiritual values, fostering moral character, and creating an environment that encourages faith-based practices and ethical behavior in education. The Guru Penggerak contributes to students' religiosity as Serving as a role model in religious behavior. Connecting lesson materials with religious values. Initiating programs like collective prayers, religious studies, or socially beneficial activities rooted in worship. Guiding students to understand and apply religious values in daily life.Creating a school environment that supports religious practices. Keywords: Guru Penggerak, Religius, Learning.